Analisis Kelayakan Penyaluran Kredit Konsumtif Dan Kredit Produktif Pada Bank Konvensional Yang Terdaftar Di Bursa Efek Indonesia Terhadap Roa Perbankan Sebelum Dan Sesudah Pandemi Covid-19 - Mhd SyaifulAmri Sinaga; Heny Triastuti Kurnianingsih; Zenni Riana; Farida Khairani Lubis (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
This study aims to analyze the feasibility of disbursing consumptive credit and productive credit of conventional banks to ROA (Return On Assets) before and after the covid-19 pandemic. The population used in this study is Conventional Commercial Banks listed on the Indonesia Stock Exchange for the period 2017 to 2020. The analytical methods used in this study are Descriptive Statistical Analysis and Independent Sample T-Test. From the results of research conducted due to the COVID-19 pandemic, bank lending experienced problems with the increase in NPL (Non-Performing Loans) and had an effect on banking ROA (Return On Assets). Based on NPL (Non-Performing Loan) data, NPL has more dominantly increased than decreased after the pandemic and vice versa, the ROA (Return On Asset) of banking was dominantly decreased after the pandemic compared to before the pandemic. And also from the results of the Independent Sample T-Test conducted by NPL, it was concluded that there was no significant difference in average or mean before and after the pandemic, while ROA had a significant difference in average or mean before and after the covid-19 pandemic